Methotrexate in rheumatoid arthritis: benefits, limitations and the emerging value of subcutaneous administration. (August 2014) - Keystone, Edward; Freundlich, Bruce
Because of its efficacy and safety, methotrexate (MTX) is well established as the anchor drug for treatment of rheumatoid arthritis. Although MTX is typically administered orally, parenteral MTX offers greater bioavailability and may cause less gastrointestinal intolerability. Parenteral MTX may be considered for patients with rheumatoid arthritis who experience an inadequate response to oral MTX at the highest tolerated dose; however, its use remains low in the USA. To facilitate the administration of subcutaneous MTX, a state of the art MTX auto-injector that enables patients to self-administer prespecified doses of MTX subcutaneously was recently developed. This auto-injector may improve patient adherence and the ability to reach an optimally effective MTX dose, thereby allowing more patients with rheumatoid arthritis to obtain the maximum benefit from MTX.